Twisted : [compact disc, unabridged] : a novel - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels., 2004)
When a brutal murder is scheduled for June 28th, detective Petra Connor must find the serial killer who, so far, has evaded the police.